2021
DOI: 10.1101/2021.04.04.438388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profiling of transcribedcis-regulatory elements in single cells

Abstract: Profiling of cis-regulatory elements (CREs, mostly promoters and enhancers) in single cells allows the interrogation of the cell-type and -state specific contexts of gene regulation and genetic predisposition to diseases. Here we demonstrate single-cell RNA-5′end-sequencing (sc-end5-seq) methods can detect transcribed CREs (tCREs), enabling simultaneous quantification of gene expression and enhancer activities in a single assay with no extra cost. We show enhancer RNAs can be effectively detected using sc-end5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…This type of analysis is compatible with single cell 5′ paired-end chemistry (SC5P-PE, 10X Genomics), but will not work with libraries that only use read 2 for alignment (SC5P-R2, 10X Genomics). We analyzed two control and two DKD snRNA-seq libraries with SC5P-PE sequencing to identify de novo transcriptional start sites in CRE using Single Cell Analysis of Five-prime Ends (SCAFE) 30,31 . SCAFE analyzes the 5′ end of RNA transcripts to identify reads mapping to the junction between the TSO and cDNA sequence to localize TSS within tCRE after filtering false positives with a logistic regression classifier.…”
Section: Cell-specific Transcribed Cis-regulatory Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of analysis is compatible with single cell 5′ paired-end chemistry (SC5P-PE, 10X Genomics), but will not work with libraries that only use read 2 for alignment (SC5P-R2, 10X Genomics). We analyzed two control and two DKD snRNA-seq libraries with SC5P-PE sequencing to identify de novo transcriptional start sites in CRE using Single Cell Analysis of Five-prime Ends (SCAFE) 30,31 . SCAFE analyzes the 5′ end of RNA transcripts to identify reads mapping to the junction between the TSO and cDNA sequence to localize TSS within tCRE after filtering false positives with a logistic regression classifier.…”
Section: Cell-specific Transcribed Cis-regulatory Elementsmentioning
confidence: 99%
“…We used SCAFE (1.0) to analyze single nucleus 5′ paired-end chemistry libraries obtained from two DKD samples and two previously published control samples (GSE151302) 30 . Transcribed cis-regulatory elements (tCRE) were called in individual libraries using the scafe.worfklow.sc.solo function with default parameters.…”
Section: Single Cell Analysis Of Five-prime Ends With Scafementioning
confidence: 99%
“…As an application of this technology, he discussed the SINEUPs, a novel group of non-coding antisense lncRNAs that enhance the translation of proteins transcribed from the region they overlap and can be used as a targeted therapy to rescue the altered gene expression. He indicated that the future is for genomics at the single-cell level and in accordance, his group is currently building a regulatory and transcriptional map at the single-cell level in the Human Cell Atlas (HCA) project which will facilitate the comprehension of biology (11). Eventually, an overview of novel advancement in ncRNAs in different disciplines was provided by the speakers.…”
Section: Ncrnas Shaping the Future Of Humankindmentioning
confidence: 99%
“…This type of analysis is compatible with single cell 5' paired-end chemistry (SC5P-PE, 10X Genomics), but will not work with libraries that only use read 2 for alignment (SC5P-R2, 10X Genomics). We analyzed two healthy control and two DKD snRNA-seq libraries with SC5P-PE sequencing to identify de novo transcriptional start sites in CRE using Single Cell Analysis of Five-prime Ends (SCAFE) (36,37). SCAFE analyzes the 5' end of RNA transcripts to identify reads mapping to the junction between the TSO and cDNA sequence to localize TSS within tCRE after filtering false positives with a logistic regression classifier.…”
Section: Cell-specific Transcribed Cis-regulatory Elementsmentioning
confidence: 99%
“…We used SCAFE to analyze single nucleus 5' paired-end chemistry libraries obtained from two DKD samples and two previously-published healthy control samples (GSE151302) (36). Transcribed cisregulatory elements (tCRE) were called in individual libraries using the scafe.worfklow.sc.solo function with default parameters.…”
Section: Single Cell Analysis Of Five-prime Ends With Scafementioning
confidence: 99%